The Influence Of Financial Literacy, Lifestyle, And Income Of Parental On The Financial Behavior Of Students In A Cashless Society In The Faculty Of Economics And Business Of Public Universities In Surabaya City - Dzakiyah, Annisa Aliyyatud; Widajantie, Tituk Diah (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Purpose: to examine how students at Surabaya State University's Faculty of Economics and Business behave financially in a cashless world in relation to their financial knowledge, lifestyle, and parental income. Methodology: A survey design and a quantitative methodology are used in this study. Questionnaires were given to 100 students in order to gather data. The Smart Partial Least Squares (PLS) method was applied to the data analysis. Results: Hypothesis testing revealed that X1, X2, and X3 influence financial behavior (Y), with a p-value of under 0.05. Findings: The three variables (X) account for 75.5% of the financial behavior variable, according to the R-squared value of 0.755. Novelty: This study is unique because it examines a topic that hasn't been extensively researched before: financial literacy, lifestyle, and parental income in the setting of a cashless society. Originality: In light of the shift to a cashless society, this study provides students at State Universities' Faculty of Economics and Business in Surabaya City with a fresh viewpoint on money management. Conclusion: In a cashless environment, student financial behavior is influenced by financial literacy, lifestyle, and parental income. Type of Paper: Empirical Research Paper.